2015
DOI: 10.1021/acs.est.5b03777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exposure to WwTW Effluents over Two Generations on Sexual Development and Breeding in Roach Rutilus rutilus

Abstract: Exposure to environmental estrogens in wastewater treatment works (WwTW) effluents induces feminized responses in male fish, including the development of eggs in male testes. However, the impacts on the offspring of exposed fish are not well understood. In this study, we examined whether roach (Rutilus rutilus) from mothers that had been exposed to an undiluted WwTW effluent from early life to sexual maturity had altered susceptibility to gonadal feminization and an impaired capacity to reproduce. For males fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
13
0
1
Order By: Relevance
“…Finally, although the severity of intersex in roach appears to increase with age, it should be pointed out that mildly feminized roach exposed to estrogens for less than a full life cycle are probably not reproductively compromised. This was demonstrated by Hamilton et al (2015) who showed experimentally that the male offspring of STW effluent-exposed females had only weakly feminized testes after exposure to 100% STW effluent for up to 3 years and 9 months, and they were able to reproduce normally. Furthermore, there was no evidence that the exposure history of the females had any influence on the reproductive performance of their male offspring.…”
Section: Feminisation Of Fish Amphibians and Reptiles Related To Sementioning
confidence: 93%
“…Finally, although the severity of intersex in roach appears to increase with age, it should be pointed out that mildly feminized roach exposed to estrogens for less than a full life cycle are probably not reproductively compromised. This was demonstrated by Hamilton et al (2015) who showed experimentally that the male offspring of STW effluent-exposed females had only weakly feminized testes after exposure to 100% STW effluent for up to 3 years and 9 months, and they were able to reproduce normally. Furthermore, there was no evidence that the exposure history of the females had any influence on the reproductive performance of their male offspring.…”
Section: Feminisation Of Fish Amphibians and Reptiles Related To Sementioning
confidence: 93%
“…Entry of EDCs into freshwater environments may occur via point source discharges of domestic or industrial effluents and/or from diffuse land run off from roads and agriculture, and are of increasing environmental concern due to widespread reports of effects on wildlife, including fish (Guillette Jr et al 1995;Jobling et al 1998;Matthiessen & Gibbs 1998;Berg et al 2016). Reproductive effects in fish resulting from EDC exposure have been reported widely, and they include physiological alterations in gonads resulting in intersex (presence of both male and female structures within the same gonad (Jobling et al 1998;Tetreault et al 2011;Jobling et al 2002)), alterations in reproductive behavior (Weis & Weis 1974;Mathers et al 1985;Brown et al 1987;Saglio & Trijasse 1998;Bell 2004) and/or reproductive output (Ankley et al 2003;Nash et al 2004;Paulos et al 2010), each of which can impair individual reproductive success (Jobling et al 2002;Harris et al 2011;Tyler et al 2012;Hamilton et al 2015). However, it is less clear how these individual effects may impact the sustainability of fish populations in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…Current approaches for the environmental risk assessment (ERA) of chemicals, including EDCs, lack certainty for protecting wildlife populations, because of differences in species sensitivity, natural variability in population numbers over time, differences in density dependent regulation, and difficulty in defining adverse (unsustainable) population-level effects (Hamilton et al 2015). Typically ERA relies on the application of (often arbitrary) assessment, or uncertainty, factors to extrapolate from laboratory derived no observed effect concentrations, in model test organisms, to the protection of wild populations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations